Performance measurement in a Lean organization: the case of the Wiremold company. Issue 2 (15th February 2022) - Grasso, Lawrence
Abstract : Theoretical basis: Critical analysis of observed practice. Research methodology: Field study. Learning outcomes: To expose accounting and MBA students to Lean management and the performance measures that support Lean management by presenting a case of a comprehensive and very successful Lean transformation; to give accounting and MBA students the opportunity to construct a strategy map and a balanced scorecard based on a rich case description; and to critically assess the suitability of balanced scorecards for a company that embraces Lean management. Case overview/synopsis: The case describes a comprehensive transformation from conventional management to Lean management and business practices, with an emphasis on the largely non-financial performance measures used to support the transformation. Around the time of the Lean transformation, the balanced scorecard, a multi-dimensional measurement approach, was introduced to address the problems of excessive reliance on financial performance measures. Students are asked to compare and contrast Wiremold's approach to the balanced scorecard. Complexity academic level: Graduate or upper level undergraduate courses in cost accounting, managerial accounting and strategic management.